Pengaruh Celebrity Endorsement Terhadap Keputusan Menginap Di Cottage Daarul Jannah - Superwiratni, Superwiratni (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
This research can be reference in the promotion of the use of celebrity endorser of guests staying at the Cottage Daarul Jannah. Formulation of the problem in the study of how the influence of celebrity endorser views of four dimensions: visibility, credibility, attraction, power of guests staying at the Cottage Daarul Jannah. By using the t test or testing in partial dimensions, visibility and credibility in the variable Celebrity endorsement do not affect significantly, whereas the dimension of the attraction and power has influence significantly. Testing by using the F test simultaneously or together the whole dimension of the celebrity endorsement effect significantly against the decision of the guest's stay